Authentication of processed meat products by peptidomic analysis using rapid ambient mass spectrometry - Montowska, Magdalena; Alexander, Morgan R.; Tucker, Gregory A.; Barrett, David A. (Elsevier, 2015)
We present the application of a novel ambient LESA-MS method for the authentication of processed meat products. A set of 25 species and protein-specific heat stable peptide markers has been detected in processed samples manufactured from beef, pork, horse, chicken and turkey meat. We demonstrate that several peptides derived from myofibrillar and sarcoplasmic proteins are sufficiently resistant to processing to serve as specific markers of processed products. The LESA-MS technique required minimal sample preparation without fractionation and enabled the unambiguous and simultaneous identification of skeletal muscle proteins and peptides as well as other components of animal origin, including the milk protein such as casein alpha-S1, in whole meat product digests. We have identified, for the first time, six fast type II and five slow/cardiac type I MHC peptide markers in various processed meat products. The study demonstrates that complex mixtures of processed proteins/peptides can be examined effectively using this approach.